Prospective Evaluation of a New Aspergillus IgG Enzyme Immunoassay Kit for Diagnosis of Chronic and Allergic Pulmonary Aspergillosis - C. Dumollard; Sébastien Bailly; Sylvain Perriot; Marie‐Pierre Brenier‐Pinchart; C. Saint‐Raymond; B. Camara; Jean‐Pierre Gangneux; Florence Persat; Stéphane Valot; Frédéric Grenouillet; Hervé Pelloux; Claudine Pinel; et al. (2016)
Anti-Aspergillus IgG antibodies are important biomarkers for the diagnosis of chronic pulmonary aspergillosis (CPA) and allergic bronchopulmonary aspergillosis (ABPA). We compared the performance of a new commercial enzyme immunoassay (EIA) (Bordier Affinity Products) with that of the Bio-Rad and Virion\Serion EIAs. This assay is novel in its association of two recombinant antigens with somatic and metabolic antigens of Aspergillus fumigatus In a prospective multicenter study, 436 serum samples from 147 patients diagnosed with CPA (136 samples/104 patients) or ABPA (94 samples/43 patients) and from 205 controls (206 samples) were tested. We obtained sensitivities of 97%, 91.7%, and 86.1%, and specificities of 90.3%, 91.3%, and 81.5% for the Bordier, Bio-Rad, and Virion\Serion tests, respectively. The Bordier kit was more sensitive than the Bio-Rad kit (P < 0.01), which was itself more sensitive than the Virion\Serion kit (P = 0.04). The Bordier and Bio-Rad kits had similar specificity (P = 0.8), both higher than that of the Virion\Serion kit (P = 0.02). The area under the receiver operating characteristic (ROC) curves confirmed the superiority of the Bordier kit over the Bio-Rad and the Virion\Serion kits (0.977, 0.951, and 0.897, respectively; P < 0.01 for each comparison). In a subset analysis of 279 serum samples tested with the Bordier and Bio-Rad kits and an in-house immunoprecipitin assay (IPD), the Bordier kit had the highest sensitivity (97.7%), but the IPD tended to be more specific (71.2 and 84.7%, respectively; P = 0.10). The use of recombinant, somatic, and metabolic antigens in a single EIA improved the balance of sensitivity and specificity, resulting in an assay highly suitable for use in the diagnosis of chronic and allergic aspergillosis.